Mechanical stress enhances CD9 expression in cultured podocytes - Blumenthal, Antje; Gretz, Norbert (American journal of physiology. Renal physiology, 2015)
Elevated glomerular pressure represents a high risk for the development of severe kidney diseases and causes an increase in mechanical load to podocytes. In this study, we investigated whether mechanical stress alters gene expression in cultured podocytes using gene arrays. We found that tetraspanin CD9 is significantly upregulated in cultured podocytes after mechanical stress. The differential expression of CD9 was confirmed by RT-PCR and Western blotting under stretched and unstretched conditions. Furthermore, mechanical stress resulted in a relocalization of CD9. To get an insight into the functional role of CD9, podocytes were transfected with pEGFP-CD9. The expression of CD9 induced the formation of substratum-attached thin arborized protrusions. Ca2+ depletion revealed that podocytes overexpressing CD9 possess altered adhesive properties in contrast to the control transfected cells. Finally, elevated CD9 expression increased migration of podocytes in a wound assay. In summary, our results suggest that upregulation of CD9 may play an important role in podocyte morphology, adhesion, and migration.
Gesehen am 02.11.2017